Eggshell Conductance and Incubator Ventilation as Factors in Embryo Survival and Poult Quality - Christensen, V.L.; Wineland, M.J.; Ort, D.T.; Mann, K.M. (International Journal of Poultry Science, 2005)
Eggshell conductance (G) and incubator ventilation (VENT) were hypothesized to affect embryo viability and growth of poults following hatching. Nearly 6,000 eggs were weighed on the day of oviposition to determine eggs of like weight but of different G. From the 6,000 eggs, 4,000 were selected that were within 2 standard deviations of the mean. The eggs were randomly divided equally between two incubator cabinets. One cabinet operated with a closed VENT and a second operated with it open. At the completion of the 24th day of development, all eggs were weighed a second time to determine eggshell G. Three groups were formed at that time exhibiting high (Hi), average (Avg) or low (Low) G. The eggs within each group were placed into hatching trays of 100 eggs each and placed into he same incubation cabinet for hatching. Weights were recorded for cardiac, hepatic and intestinal tissues, and blood was collected from each treatment. The tissues were subsequently assayed for energy substrates. Embryo viability was noted and growth was observed up to 6 wk of age. More embryos in eggs of Hi or Avg G survived than did those in Low G eggs, but neonates at 6 wk from Hi G eggs weighed less than those from Avg or Low G eggs. Low G embryos had reduced heart, liver and intestinal weight and function. Embryo thyroid hormone concentrations were elevated in Hi G eggs but suppressed by Low G and Closed VENT. Thus, in the developmental process of the embryonic turkey, G may determine energy balance and maturity of each hatchling and may affect its survival and growth rates following hatching.